2013
DOI: 10.1159/000350517
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Nef Interacts with HCV Core, Recruits TRAF2, TRAF5 and TRAF6, and Stimulates HIV-1 Replication in Macrophages

Abstract: Tumor necrosis factor receptor-associated factor (TRAF) signaling plays a central role in many biological activities, such as the regulation of immune and inflammatory responses and control of apoptosis, which are key events in the pathogenesis of the human immunodeficiency virus (HIV)-1 and the hepatitis C virus (HCV) infections. Here we show that TRAF2, TRAF5 and TRAF6 interact with the HIV-1 Nef protein, an immunomodulatory viral protein expressed and released by cells infected by the virus. We also found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 51 publications
0
34
0
Order By: Relevance
“…Because TRAF6 is one component of the IFN signaling pathway that controls viral replication (Sirois et al, 2011;Khan et al, 2013), but also a target of miR-146a in immune cells (Taganov et al, 2006;Boldin et al, 2011), we analyzed TRAF6 expression at both mRNA and protein level in resting and activated CD4 þ T lymphocytes, to examine miR-146a activity in these cells. Our data are significant of a posttranscriptional control of TRAF6 mRNA translation by miR146a targeting, as the decrease of miR-146a results in an increase of TRAF6 protein level during activation of CD4 þ T lymphocytes, independently of HIV-1 infection, as also observed for CXCR4 in these cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because TRAF6 is one component of the IFN signaling pathway that controls viral replication (Sirois et al, 2011;Khan et al, 2013), but also a target of miR-146a in immune cells (Taganov et al, 2006;Boldin et al, 2011), we analyzed TRAF6 expression at both mRNA and protein level in resting and activated CD4 þ T lymphocytes, to examine miR-146a activity in these cells. Our data are significant of a posttranscriptional control of TRAF6 mRNA translation by miR146a targeting, as the decrease of miR-146a results in an increase of TRAF6 protein level during activation of CD4 þ T lymphocytes, independently of HIV-1 infection, as also observed for CXCR4 in these cells.…”
Section: Discussionmentioning
confidence: 99%
“…TRAF6 protein is also downmodulated in U937(miR-146a) cells (our unpublished data) and may be involved in resistance to HIV-1 infection that we observed with these cells. Therefore, as a recent study performed on human macrophages has shown that the knockdown of TRAF6, but also TRAF2 and 5, results in decreased NF-kB activation and reduces HIV-1 replication in monocyte-derived macrophages (Khan et al, 2013), understanding the role of the miR-146a/ TRAF6 axis in HIV-1 infection of Mo leukemic cells and CD4 þ T lymphocytes, in the context of the complex TRAF signaling, requires future dedicated studies.…”
Section: Discussionmentioning
confidence: 99%
“…HCV core has been shown to mediate repression of the HIV-1 protein Tat-mediated transactivation of HIV-1 long terminal repeat (LTR) in a hepatoma cell line [25]. In contrast, Khan et al [26] have shown that HCV core and HIV-1 protein Nef upregulated HIV-1 LTR-driven luciferase expression in a transiently-transfected human monocytic cell line. Strikingly, the potential role of HCV core on HIV-1 infectivity in the context of infection, rather than plasmid-based transcription analysis, remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of the Journal of Innate Immunity , there are four review articles that address the manifold functions of this fascinating cytokine that has lately attracted much attention (for a review see Zheng et al [1]). Like many other inflammatory mediators, the role of interferons in health and disease is tightly regulated [2], so it is not surprising that inflammatory reactions influence disease progression in the complications mentioned above, namely, allergic reactions [3,4], virus infections [5,6] and cancer [7]. Though the role of IFN-λ in the context of these conditions has been discussed previously [8,9,10], much more research is required to completely understand its physiological and pathological impact.…”
mentioning
confidence: 99%